Defective initiation of glycosaminoglycan synthesis due to B3GALT6 mutations causes a pleiotropic Ehlers-Danlos-syndrome-like connective tissue disorder - Malfait, Fransiska; Kariminejad, Ariana; Van Damme, Tim; Gauche, Caroline; Syx, Delfien; Merhi-Soussi, Faten; Gulberti, Sandrine; Symoens, Sofie; Vanhauwaert, Suzanne; Willaert, Andy; Bozorgmehr, Bita; Kariminejad, Mohamad Hasan; et al. (The American journal of human genetics, 2013)
Proteoglycans are important components of cell plasma membranes and extracellular matrices of connective tissues. They consist of glycosaminoglycan chains attached to a core protein via a tetrasaccharide linkage, whereby the addition of the third residue is catalyzed by galactosyltransferase II (β3GalT6), encoded by B3GALT6. Homozygosity mapping and candidate gene sequence analysis in three independent families, presenting a severe autosomal-recessive connective tissue disorder characterized by skin fragility, delayed wound healing, joint hyperlaxity and contractures, muscle hypotonia, intellectual disability, and a spondyloepimetaphyseal dysplasia with bone fragility and severe kyphoscoliosis, identified biallelic B3GALT6 mutations, including homozygous missense mutations in family 1 (c.619G>C [p.Asp207His]) and family 3 (c.649G>A [p.Gly217Ser]) and compound heterozygous mutations in family 2 (c.323_344del [p.Ala108Glyfs∗163], c.619G>C [p.Asp207His]). The phenotype overlaps with several recessive Ehlers-Danlos variants and spondyloepimetaphyseal dysplasia with joint hyperlaxity. Affected individuals’ fibroblasts exhibited a large decrease in ability to prime glycosaminoglycan synthesis together with impaired glycanation of the small chondroitin/dermatan sulfate proteoglycan decorin, confirming β3GalT6 loss of function. Dermal electron microcopy disclosed abnormalities in collagen fibril organization, in line with the important regulatory role of decorin in this process. A strong reduction in heparan sulfate level was also observed, indicating that β3GalT6 deficiency alters synthesis of both main types of glycosaminoglycans. In vitro wound healing assay revealed a significant delay in fibroblasts from two index individuals, pointing to a role for glycosaminoglycan defect in impaired wound repair in vivo. Our study emphasizes a crucial role for β3GalT6 in multiple major developmental and pathophysiological processes.